Effect Of Dexmedetomidine Added To Intrathecal Hyperbaric Bupivacaine Versus Bupivacaine Alone On Mean Postoperative Analgesia After Spinal Saddle Block - Khalid, Muhammad; Feroze, Faheem; Faheem, Muhammad Shaheer Bin; Faheem, Sadia; Khalid, Maliha; Farooq, Saeed (Journal of Rawalpindi Medical College, 2025)
Objective: Spinal saddle anaesthesia is the most prevalent method for perineal surgeries. Dexmedetomidine, a unique medication that acts on α2-adrenergic receptors in the spinal cord, relieves pain. The goal is to assess the efficacy of intrathecal dexmedetomidine in combination with bupivacaine. Methods: A total of 60 patients undergoing elective uncomplicated peri anal surgeries were included in the study. 30 patients were in the 0.75% hyperbaric Bupivacaine group (Group A) and 30 patients were in the 0.75% hyperbaric Bupivacaine with Dexmedetomidine 5 mcg group (Group B). Intensity of pain was analysed through the Visual analogue pain score VAS which was described to the patients on a scale from 0-10 (No pain to severe pain). Mean analgesia duration was measured from time 0 of SSB until the patient asked for additional pain killers (VAS score >4). Results: The mean duration of surgery was 29.866±1.87 minutes in group A and 28.866±2.06 minutes in group B. Motor block was of lesser duration in group A (152.90±9.09 minutes) as compared to group B (203.00±18.95 minutes) with p<0.05. Mean analgesia duration was significantly prolonged in group B (630.66±78.50 minutes) versus group A (325.33±36.67 minutes) with a statistically significant p-value. (p<0.05) Postoperatively, a lower frequency of painkiller demands was made by group B patients in 24 hours. (p<0.05) Conclusion: In SSB, Dexmedetomidine added to Bupivacaine intrathecally increases the duration of analgesia postoperatively.